Оптимізація на основі штучних імунних систем - Зайцев, Сергій; Субботін, Сергій (Видавництво Національного університету «Львівська політехніка», 2009)
The optimization method based on artificial immune system is presented. This method can be used for multimodal function optimization. It is inspired on the theory of Clonar Selection. The experiments on method testing are carried out and proved the practival applicalicability of the method.
Keywords: оптимізація; імунні системи; генетичні алгоритми